Gender and age determination through linear and volumetric measurements of the sphenoid sinus using CBCT images - Isabela Inoue Kussaba; Vitor Menani Sergi; Elen Tolentino; Wilton Takeshita; Lilian Cristina Vessoni Iwaki; Mariliani Chicarell da Silva (Acta Scientiarum. Health Sciences)
This retrospective, observational, longitudinal study carried out a morphometric analysis of CBCT images of the sphenoid sinus to evaluate whether they can be used to determine gender and age in a mixed Brazilian population. 200 CBCT scans (100 females; 100 males) were retrospectively selected and the linear (maximum height, width, length) and volumetric measurements were taken in the right and left sphenoid sinuses. The sample was also divided according to age in 18-40 (n = 123) and>40 years (n = 77). The sinus volume was calculated using a formula (a multivariate discriminant analysis) and a software program, and the results were compared. All data were subjected to statistical analysis (p<0.05). Only the volume of the right sphenoid sinus showed a statistically significant difference (p ≤ 0.05) between the genders, with lower values for females. Most measurements were higher in group 18-40 years (p<0.05). There was no difference between the volumes calculated using the formula and the software. The overall gender determination accuracy rate was 60.08%. For the>40 years group, the discriminant analysis achieved an accuracy index of 74%. Morphometric measurements of the sphenoid sinus in CBCT exams are useful for gender and age estimation in adult Brazilians. The greatest accuracy is obtained for determining age when individuals are over 40 years old.